О семействах функций с равностепенно абсолютно непрерывными интегралами - Довгошей А.А. (Український математичний журнал, 1992)
The approximation of functions from Hardy classes by bounded analytic functions is investigated. A theorem is proved, characterizing the sets of functions with equiabsolutely continuous integrals as limit points of the family of bounded subsets of the space H∞.